Effect of zinc on growth of preterm babies - Islam, Md Nazrul; Chowdhury, AK; Siddika, M; Hossain, MA; Hossain, MK (Mymensingh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Mymensingh Med J. 2009 Jan;18(1):125-130. The abstract of this article is available on the PubMed website